Design and Development of Fitastic Application based on Android Technology - Tan, Terry; PROF. MADYA Ts. Dr. MOHD FARHAN BIN MD. FUDZEE (Applied Information Technology And Computer Science, 2023)
Maintaining body fitness offers many health benefits such as weight control, reducing the risk of heart diseases, and improving mental and mood. However, it is challenging in this era of globalisation because the COVID-19 pandemic causes people not to exercise. They are not willing to spend their money to hire a fitness instructor, which will cause them to train with an ineffective plan. Apart from that, all the fitness applications that appear in the current market do not exist a concept that provides three fitness services into one application and causes the user to use three different applications to track their fitness. Therefore, ‘Fitastic’ health and fitness application is proposed to be developed. This application can help users track their fitness levels with different modules to effectively track down the user’s fitness who aged between 18 years old and above. Additionally, this project used the Agile methodology to develop the ‘Fitastic’ application. This application was developed using the Android Studio and Kotlin Programming languages. On a scale measuring the system's usability, the application obtained an 84% overall good rating from the target user after undergoing testing. The application can work efficiently and accomplish all of its goals. The final expectation is that this project would aid the user in maintaining a healthy lifestyle.